1998
DOI: 10.1136/bmj.317.7165.1054
|View full text |Cite
|
Sign up to set email alerts
|

Safety and effectiveness of nurse telephone consultation in out of hours primary care: randomised controlled trial

Abstract: 14 492 calls were received during the specified times in the trial year (7308 in the control arm and 7184 in the intervention arm) concerning 10 134 patients (10.4% of the registered population). There were no substantial differences in the age and sex of patients in the intervention and control groups, though male patients were underrepresented overall. Reasons for calling the service were consistent with previous studies. Nurses managed 49.8% of calls during intervention periods without referral to a general… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
268
1
11

Year Published

2001
2001
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 299 publications
(285 citation statements)
references
References 17 publications
5
268
1
11
Order By: Relevance
“…NTLs are also beneficial in that they reduce strain on the HCS, offer high levels of patient satisfaction, and serve as a safe, efficient, and cost-effective method of information dissemination. [19][20][21][22][23][24] Benefits can also be seen in reduced travel costs, reduced time away from school/work, and reduced childcare expenses. 17 …”
Section: Discussionmentioning
confidence: 99%
“…NTLs are also beneficial in that they reduce strain on the HCS, offer high levels of patient satisfaction, and serve as a safe, efficient, and cost-effective method of information dissemination. [19][20][21][22][23][24] Benefits can also be seen in reduced travel costs, reduced time away from school/work, and reduced childcare expenses. 17 …”
Section: Discussionmentioning
confidence: 99%
“…[11][12][13] Recent studies have reported results of randomised controlled trials of nurse telephone triage in out-of-hours primary medical care. 14,15 In one trial, nurse triage reduced GP workload by 50% and concluded that nurse telephone consultation, supported by decision support software, was as safe and effective as the standard care provided by a GP co-operative. 15 …”
mentioning
confidence: 99%
“…In the UK, a randomised control trial has found telephone triage to be associated with reduced demand for general practice services while providing the same outcomes as usual after-hours care (Lattimer et al 1998), and an overview of services of this kind has suggested that they can reduce growing demand for face-to-face GP services in the after-hours period (Munro et al 2000). Neither study found an impact on the demand for services from emergency departments.…”
Section: Cost-competitiveness Of the Servicementioning
confidence: 99%